2014
DOI: 10.1364/josaa.31.001495
|View full text |Cite
|
Sign up to set email alerts
|

Rayleigh approximation for the scattering of small partially charged sand particles

Abstract: Based on the Rayleigh approximation, this paper presents the electromagnetic scattering properties of the small partially charged isotropic sphere and those of a similar anisotropic sphere and then discusses the effect of surface charges on particles' optical properties. The numerical simulation results show that the surface charges on a charged particle can enhance the scattering of the incident waves, and the effect on an anisotropic charged sphere is much greater than that on an isotropic charged particle. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…Their conclusion at 10 GHz and 37 GHz are aligned with the previous results and it is confirmed that after for a constant value of charge-to-mass ratio the attenuation tend to increase with the charge distribution angle until a certain point beyond which the attenuation starts to decrease. The impact of medium properties, i.e., isotropic (having the same physical properties in all directions) or anisotropic (exhibiting distinct physical properties in different directions), on EM scattering was investigated in [130]. The simulations revealed that an anisotropic charged sphere has a greater influence than an isotropic one.…”
Section: H Influence Of Charges On Sds Attenuation Modelsmentioning
confidence: 99%
“…Their conclusion at 10 GHz and 37 GHz are aligned with the previous results and it is confirmed that after for a constant value of charge-to-mass ratio the attenuation tend to increase with the charge distribution angle until a certain point beyond which the attenuation starts to decrease. The impact of medium properties, i.e., isotropic (having the same physical properties in all directions) or anisotropic (exhibiting distinct physical properties in different directions), on EM scattering was investigated in [130]. The simulations revealed that an anisotropic charged sphere has a greater influence than an isotropic one.…”
Section: H Influence Of Charges On Sds Attenuation Modelsmentioning
confidence: 99%
“…From Rayleigh scattering's point of view, the amplitude of light scattered by any deep subwavelength nanostructure with primary dimension d from a beam of unpolarized light of wavelength λ is proportional to d 3 /λ 2 [98,99]. However, the phase change φ due to a ridge with height h on a surface can be approximately expressed as φ = 4πh/λ [100], indicating that the phase is more sensitive than amplitude associated with vertical subwavelength dimensions.…”
Section: Phase-based Optical Inspection Systemsmentioning
confidence: 99%
“…A few attempts to treat such models appeared only recently and introduced position-dependent conductivity [24,25]. However, separation ansatz for generating function cannot be applied to obtain a complete solution of the scalar Fig.…”
Section: Consequences Of the Theoretical Modelmentioning
confidence: 99%